The prevalence and genotype distribution of human papilloma virus in cervical squamous intraepithelial lesion and squamous cell carcinoma in Taizhou, China. Issue 28 (16th July 2021) - Jin, Rongrong; Yang, Xumei; Bao, Jingjing; Zhang, Wenyan; Dou, Rongrong; Yuan, Donglan; Yang, Qinxin; Jiang, Lin; Yu, Hong
Abstract : Abstract: Human papillomavirus (HPV) infection is a common sexually transmitted disease worldwide and the leading cause of cervical cancer. Current vaccines do not cover all HPV genotypes whereas the distribution of HPV genotypes varies in different geographic regions. The study aimed to investigate the distribution of HPV genotypes in patients with cervical squamous intraepithelial lesion (SIL) and cervical squamous cell carcinoma (SCC) in Taizhou City of Jiangsu Province, China. A total of 940 patients including 489 cases with cervical low-grade squamous intraepithelial lesions (LSIL), 356 cases with cervical high-grade squamous intraepithelial lesions (HSIL), and 95 cases with cervical SCC, underwent a biopsy or surgery in Taizhou People's Hospital between January 2019 and December 2019. The HPV testing results were retrospectively analyzed. The overall prevalence of any, high-risk, and low-risk HPV was 83.83%, 81.91%, and 12.13%, respectively. The 5 most common HPV genotypes were HPV16 (35.64%), HPV52 (16.91%), HPV58 (13.94%), HPV33 (8.94%), and HPV18 (7.98%). The prevalence of any and HR-HPV in SCC was significantly higher than those in LSIL and HSIL, while the prevalence of LR-HPV in SCC was significantly lower than those in LSIL and HSIL ( P  < .01). Single and dual HPV infections were prevalent in SCC, LSIL, and HSIL. Furthermore, the prevalence of dual HPV infection in SCC was significantly higher than those in LSIL and HSIL ( P  = .002). The HPV prevalence varied by age, being highest among women with SCC, LSIL, and HSIL aged 40 to 49 years, 40 to 49 years, and 50 to 59 years, respectively. In conclusion, the findings revealed a very high prevalence of HPV in women with cervical lesions in Taizhou. Routine HPV tests must cover all common HPV genotypes in clinical practice.